14. The Potency of Sernai (Wedelia biflora) Leaf N-hexan Extract as Analgesic Compared to Ibuprofen on Mice (Mus musculus) - Zulkarnaini Zulkarnaini; Rinidar Rinidar; Rosmaidar Rosmaidar; T. Armansyah TR; Abdul Harris; Muhammad Isa (Jurnal Medika Veterinaria, 2018)
This study aimed to determine the analgesic potential of sernai leaves n-Hexan extract on 24 male mice, aged 2-3 month with 20-25 g weighed. This study used split-plot design consisted of 6 groups. P0 as negative control was given aquades and P1 as positive control was given ibuprofen (10 mg/kg Body Weight). Treatment groups including P2, P3, P4, and P5 were given n-Hexan extract of sernai leaves with dosage of 15, 30, 45, and 60 mg/kgBW, respectively. Pain assessment was conducted using Hot Plate method. Observation of mice behaviour including licking it's front and back leg, or by jumping. This study showed there was significant difference (P0,05) between dosage and time. Duncan’s test showed P1 was significantly different (P0,05) from P2, but P3 and P5 were not significantly different from P1. P3 and P4 were significantly different (P0,05) from P2 and not significantly different from P1, while P5 was not significantly different from P3 and significantly different from P1. We can conclude that dosage of 30 and 45 mg/kgBW of n-Hexan extract of sernai leaves had analgesic potential on mice, and 60 mg/kgBW was comparable to ibuprofen as pain relieve in mice